Del oceano Atlantico Septentrional que comprende desde el equator hasta 58 [grados] de latitud norte y entre la longitud de 93 [grados] aÌ ocidente y 15 [grados] al oriente del meridiano de Cadiz. ([n.a.], 1825)
Map shows northern Atlantic Ocean ports and coastline detail, including the coastline along the Gulf of Mexico and the Pacific coastline of Central America and the northern coast of South America. Ports and coastline detail are also provided for western Africa, western Europe, Great Britain, the North Sea, and the Mediterranean Sea to the Islands of Corsica and Sardinia. Includes some dates of sightings or discoveries for islands in the Atlantic. Relief shown by hachures. Depths shown by soundings. Scale not given.